Heavy metals assessment of hospital wastewater during COVID-19 pandemic - Nova Amalia Sakina; Ahyahudin Sodri; Haryoto Kusnoputranto (Intelektual Pustaka Media Utama, 2023)
Hospital wastewater contains heavy metals that threaten environmental and human health through bioaccumulation and biomagnification. Each heavy metal contributes a different impact on human health and the environment. Monitoring the heavy metals in wastewater is essential to prevent those severe impacts. However, it is still rare for a study to assess heavy metals obtained from the discharge of hospital wastewater in Indonesia. Therefore, this study investigated 14 parameters of heavy metals in hospital wastewater. We tested wastewater quality from September 2021 to February 2022, with SNI 6989-59-2008 sampling methods with 14 parameters. Results show that over 14 parameters are still below the threshold value and other previous studies. It might be because the biological treatment used in the hospital wastewater treatment plant (HWWTP) reduces these micropollutants efficiently. The fluidized bed biofilm reactor (FBBR) system is an aerobic process with microorganisms attached to the bio-green. This technique is to form suspensions of solid particles in sparse media with gas streams for chemical or physical processes. The sewage discharge reveals the occurrence of heavy metals in hospital wastewater, even though it does not reveal a high concentration due to the effectiveness of the FBBR system in HWWTP.